2015
DOI: 10.20510/ukjpb/3/i4/89454
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites with antioxidant and photo-protective properties from Usnea roccellina Motyka, a lichen from Colombian Andes

Abstract: The antioxidant and photo-protective efficacy of the extract and isolated compounds from the lichen Usnea rocellina Motyka were evaluated. The antioxidant activity was determined by scavenging the DPPH radicals and ferric reducing power. The photo-protective property of extracts and isolated compound against ultraviolet A (UVA) and B (UVB) radiations was measured in vitro by calculation of their sun protection factor (SPF), critical wavelength and UVA ratio comparing to commercialised sunscreens (avobenzone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…EBm was less potent than positive controls (BHT and AA) to act as free radical scavenger but, it was more potent than other lichen extracts that have been a source of potent antioxidants. 15,23,24 To our knowledge, everninic acid (2), sphaerophorol carboxylic acid (3) and friedelin (4) are reported here for the first time for this species along with sphaerophorin (1) reported previously. 12 The orsellinic acid-type isolated compounds 1, 2 and 3 were better free radical scavengers than EBm; therefore, they can be considered as its active constituents.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…EBm was less potent than positive controls (BHT and AA) to act as free radical scavenger but, it was more potent than other lichen extracts that have been a source of potent antioxidants. 15,23,24 To our knowledge, everninic acid (2), sphaerophorol carboxylic acid (3) and friedelin (4) are reported here for the first time for this species along with sphaerophorin (1) reported previously. 12 The orsellinic acid-type isolated compounds 1, 2 and 3 were better free radical scavengers than EBm; therefore, they can be considered as its active constituents.…”
Section: Discussionmentioning
confidence: 54%
“…The potency (EC 50 ) of the extract of B. melanocarpum (EBm) and compounds 1 to 4 as free radical scavengers was determined at 25.0 °C using 1,1-diphenyl-2-picrylhydrazyl (DPPH • ) as free radical according to Brand-Williams et al 14 methodology and some modifications as indicated by Rojas et al 15 Butylated hydroxytoluene (BHT) and ascorbic acid (AA) were the positive controls. EtOH solutions of DPPH • and extract or compounds were mixed in different ratios and their initial absorbance and its decrease was recorded (λ 515 nm, every 15 min) until a steady state was reached.…”
Section: Determination Of Antioxidant Activity Free Radical Scavenging Activitymentioning
confidence: 99%
See 3 more Smart Citations